Investigation of the efficacy and safety of wild- type and triple-gene knockout pig RBC transfusions in nonhuman primates - Roh, Juhye; Hwang, Jeong Ho; Park, Sangkeun; Lee, Haneulnari; Park, Eun Mi; Lee, Hye Won; Lee, Ju Young; Shim, Joohyun; Choi, Kimyung; Kang, Hee Jung (Frontiers in Immunology, 2024)
Decreasing rates of blood donation and close margins between blood supply and demand pose challenges in healthcare. Genetically engineered pig red blood cells (pRBCs) have been explored as alternatives to human RBCs for transfusion, and triple-gene knockout (TKO) modification improves the compatibility of pRBCs with human blood in vitro. In this study, we assessed the efficacy and risks of transfusing wild-type (WT)-and TKO-pRBCs into nonhuman primates (NHPs). Methods: Blood from O-type WT and TKO pigs was processed to produce pRBCs for transfusion, which were transfused or not into NHPs (n=4 per group: WT, TKO, and control) after 25% total blood volume withdrawal: their biological responses were compared. Hematological, biochemical, and immunological parameters were measured before, immediately after, and at intervals following transfusion. Two months later, a second transfusion was performed in three NHPs of the transfusion group. Results: Transfusion of both WT-and TKO-pRBCs significantly improved RBC counts, hematocrit, and hemoglobin levels up to the first day post-transfusion, compared to the controls. The transfusion groups showed instant complement activation and rapid elicitation of anti-pig antibodies, as well as elevated liver enzyme and bilirubin levels posttransfusion. Despite the higher agglutination titers with WT-pRBCs in the pre-transfusion crossmatch, the differences between the WT and TKO groups were not remarkable except for less impairment of liver function in the TKO group. After the second transfusion, more pronounced adverse responses without any hematological gain were observed. Conclusions: WT-and TKO-pRBC transfusions effectively increased hematologic parameters on the first day, with rapid clearance from circulation thereafter. However, pRBC transfusion triggers strong antibody responses, limiting the benefits of the pRBC transfusion and increasing the risk of adverse reactions.